Could Towel bath reduce aggressiveness in patient with dementia? Results from a crossover trial - Roberta Lodini; Stefano Terzoni; Agostino D'Antuono; Elena Sala; Giancarlo Celeri; Mauro Parozzi; Paolo Ferrara; Laura DiPrisco; Lara Carelli; Giada Cocciolo (Dissertation Nursing, 2022)
BACKGROUND: Bathing is one of the most intimate activities during which persons with dementia are cared for. The literature suggests that 20-40% of patients with cognitive impairment, hospitalized in long-term facilities, may react with aggressive behaviours.